Battambang City, Cambodia: From a small colonial settlement to an emerging regional centre. (April 2019) - Han, Sun Sheng; Lim, Ymeng
Abstract: Battambang City stands out in representing the millions of small urban settlements which are important carriers of urbanisation in the 21st century. Its trajectory of development was shaped by regional and international powers and domestics politics, while the current conditions are characterised by a strong urge to develop its economy but a severe lacking of both soft and hard capabilities. The city profile demonstrates the development pathway of Battambang City from a small colonial settlement to a regional administrative, business and transportation centre, and the current administrative and planning systems that influence its economy and land-use. Key issues that have to be addressed include adequate provision of regional and urban infrastructure, heritage conservation, informal settlements, and protection of the endangered natural setting especially along the Sangker River.